Pengembangan Produksi Benih Sumber Varietas Unggul Baru (VUB) Padi Umur Genjah Hasil Di Provinsi Sumatera Selatan - Waluyo; Suparwoto; Johanes. A; Nur Wahyu S (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
Superior varieties are one of the technologies that play an important role in increasing the quantity and quality of agricultural products. The real contribution of superior varieties to increasing national rice production was reflected in the achievement of rice self-sufficiency in 1984. This was related to the characteristics possessed by superior varieties of rice, including high yields, resistance to major pests and diseases, early maturity so that can be developed to increase the cropping index, and taste good (fluffy) rice with relatively high protein content. The purpose of this activity is to develop seed production of new superior varieties at early maturity resulting from the innovation of the Agricultural Research and Development Agency. The source seed production development activity was carried out from October 2021 to April 2022 in irrigated rice fields, Sidomulyo Village, Belitang District, Ogan Komering Ulu Timur Regency. By using the Cakrabuana variety, White label seed class (FS) with a planting area of 5 ha. The data collected includes growth and yield performance data. The data collected were tabulated and analyzed (quantitatively). Observations of yield components carried out 1 week before harvest, showed an average plant height of 114.6 cm with the number of productive tillers of 29.2 stems/clump. While the average panicle length obtained was 27.06 cm with an average number of grain contents per panicle as many as 143.2 grains/panicle. The weight of 1000 grains of grain is 29 grams, productivity reaching 10.2 tons gkp/ha (8.5 tons gkg/ha).